2023
DOI: 10.3233/jad-220924
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia Symptoms and Biomarkers of Alzheimer’s Disease in the Community

Abstract: Background: Insomnia is one of the most common sleep disorders yet its relationship to the biology of Alzheimer’s disease remains equivocal. Objective: We investigated the cross-sectional relationship between insomnia symptom severity and cerebrospinal fluid (CSF) concentrations of Alzheimer’s disease biomarkers in a cognitively unimpaired middle-aged community sample. Methods: A total of 63 participants from the Healthy Brain Project (age = 59±7 years; 67% women) completed a lumbar puncture and two weeks of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Clinical evidence suggests that insomnia as a symptom of AD is highly detrimental, predicting rapid hospitalization and death [ 12 , 24 ]. Recent studies suggest that insomnia, especially at a young age, contributes to the early manifestation of the disease and may act as a triggering factor in the development of early-onset AD [ 3 , 26 ]. Our data showed that 5xFAD mice, which serve as a model for the familiar form of AD, were unable to tolerate prolonged sleep deprivation compared to their non-transgenic littermates (WT).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical evidence suggests that insomnia as a symptom of AD is highly detrimental, predicting rapid hospitalization and death [ 12 , 24 ]. Recent studies suggest that insomnia, especially at a young age, contributes to the early manifestation of the disease and may act as a triggering factor in the development of early-onset AD [ 3 , 26 ]. Our data showed that 5xFAD mice, which serve as a model for the familiar form of AD, were unable to tolerate prolonged sleep deprivation compared to their non-transgenic littermates (WT).…”
Section: Discussionmentioning
confidence: 99%